The Community Participation in Improving Pendapatan Asli Desa (PADes) and Strengthening the Community Economy in Cibereum Village, Cisarua Districts, Bogor Regency - Yuswarni; Achmad Firdaus; Riko Riyanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
As is well known, Cibereum Village is the largest Dairy Cattle producing village in Indonesia with a total of 103 dairy cows. Every day it will produce 500-1000 kg of pure milk. Apart from that, there is also Usaha Mikro, Kecil dan Menengah (UMKM)/ Micro, Small, and Medium Enterprises which is the mainstay for the village of Cibereum, such as the production of hotel sandals, typical village souvenirs. In realizing development goals, all regional potentials must be explored, developed, and put to good use. This is to increase Pendapatan Aasli Desa (PADes)/ Village Original Income. PADes includes the results of village businesses, the results of separated village wealth management, the results of self-help and community participation, the results of mutual cooperation, other legitimate village original income (Nurcholis, 2011: 82). In increasing Village Original Income, community participation is expected to contribute to decision making, policy implementation, monitoring, and evaluation. The development thinking framework currently being developed is an empowerment thinking framework that is centered on community participation.According to Dewi, Fandeli, and Baiquni (2013), community participation is a right owned by the community to take part in decision-making at all stages of the development process, starting from the initial planning, implementation, monitoring, and environmental preservation. Here the community is not only the recipient of facilities and benefits but as the subject of sustainable development. Community participation is one of the factors that influence the success of rural community development. In this regard, the authors are interested in conducting research on how community participation or participation in increasing PADes and what factors are obstacles in efforts to increase community participation in increasing PADes and strengthening the community's economy in Cibereum Village, Cisarua District, Bogor Regency. This study uses qualitative methods with descriptive data. Descriptive data is generated in the form of spoken or written words from people and observed behavior or descriptions of facts that are systematic, factual and accurate which explain community participation in increasing PADes. This research took place in Cibereum Village, Cisarua District, Bogor Regency. The samples in the study were local residents, business actors, UMKM, and the village government through direct interviews in the field. Data obtained from the field stated that the Cibereum village community played an active role in increasing PADesa. This is proven by the many household industries and micro-business actors in Cibereum Village such as animal husbandry and cow's milk production, production of hotel slippers and typical village souvenirs. The active role of the community and the many types of businesses in Cibereum Village have resulted in an increase in the village's original income, followed by strengthening the community's economy in Cibereum Village, Cisarua District, Bogor Regency. Some of the factors that influence community participation in increasing PADesa include (Pangestu, 1995) namely internal factors, including individual characteristics including age, level of education, total family burden, total income, and group experience. External factors include the relationship that is built between the project manager and the target which can affect participation because the target will voluntarily get involved in a project if the management response is positive and benefits them. Watson in Soetomo 2008 one of the inhibiting factors for community participation is dependency. The dependence of the community on the government in implementing development activities is an obstacle to realizing community participation or active involvement. Another obstacle faced is that the community is not familiar with the Badan Usaha Milik Desa ( BUMdes)/ village-owned enterprises system so that the management is not optimal because so far the community has used the Koperasi Unit Desa (KUD)/ Village Unit Cooperative system. the Covid 19 Pandemic which has been going on for the last three years, it has caused many business actors to close their businesses because there is no economic turnover.